2017
DOI: 10.21570/edgg.bull.33.15-23
|View full text |Cite
|
Sign up to set email alerts
|

Steppe protected areas on the territory of Ukraine in the context of the armed conflict in the Donbas region and Russian annexation of the Crimean Peninsula

Abstract: We are pleased to present the new issue of the EDGG Bulletin, which comprises the invitation for the next EDGG Field Workshop in the Central Apennine mountains, in Italy. EDGG Research Expeditions/Field Workshops have been conducted annually since 2009, and have contributed to the development of a large body of standardized data. This issue includes a call for data to be added to this dataset, which would be used for analyses of biodiversity patterns and their drivers across biogeographical gradients. The Bull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
3
0
3
Order By: Relevance
“…Also within the European continent there is an example of a recent conflict that is still going on, the War in Eastern Ukraine (2014-present). This war has affected significant percentages of both forests and steppes within the region-including those located on nature reserves, by means of direct effects (explosions and fires, and damage due to the passage of heavy military machinery and construction of fortifications and trenches) or indirectly by dismantling nature reserves administration (Vasyliuk et al, 2017). A number of additional cases can be found in the Enzler (2006) webpage about the environmental effects of wars and incidents leading to war that have occurred in the 20th and 21st century.…”
Section: (A) (B)mentioning
confidence: 99%
“…Also within the European continent there is an example of a recent conflict that is still going on, the War in Eastern Ukraine (2014-present). This war has affected significant percentages of both forests and steppes within the region-including those located on nature reserves, by means of direct effects (explosions and fires, and damage due to the passage of heavy military machinery and construction of fortifications and trenches) or indirectly by dismantling nature reserves administration (Vasyliuk et al, 2017). A number of additional cases can be found in the Enzler (2006) webpage about the environmental effects of wars and incidents leading to war that have occurred in the 20th and 21st century.…”
Section: (A) (B)mentioning
confidence: 99%
“…Under the direction of Editor-in-Chief Anna Kuzemko, Deputy Editor-in-Chief Idoia Biurrun and the Editorial Board, the Bulletin now goes beyond announcements and reports of EDGG activities and short communications by our members and also regularly publishes full articles in the categories "Research paper", "Forum paper", "Review" and "Report", all of which receive a digital object identifier (DOI) to make them easily retrievable from literature databases, such as ResearchGate. Notable articles of the reporting period include the methodological paper on the EDGG multiscale sampling (Dengler et al 2016b), an overview of mean and maximum richness values found in dry grasslands of different regions at different grain sizes (Dengler et al 2016a) and a forum paper reflecting on the impact of armed conflicts on protected steppe areas in Ukraine (Vasyliuk et al 2016).…”
Section: Publication Activities Associated With Edgg In 2016-2017mentioning
confidence: 99%
“…In EDGG Bulletin 33, we reported on the imminent threat of ploughing to the landscape reserve "Tarutyns'kyj Steppe" in Ukraine (Odesa Oblast) at the end of 2016 (Vasyliuk et al 2017). Within a few days after the news emerged of ploughing at the Tarutyns'kyj Steppe, this turned into the major environmental topic of 2016 and has evolved into the largest environmental campaign in Ukraine for the entire year.…”
Section: Forum Papermentioning
confidence: 99%